IKAN TUNA SIRIP KUNING (Thunnus albacores) DI PERAIRAN ZONA EKONOMI EKSKLUSIF INDONESIA SAMUDERA HINDIA SELATAN JAWA TIMUR - Hermawan, David; Boer, Mennofatria; Dahuri, Rokhmin; Budiharsono, Sugeng; Farid Ma’ruf, Widodo (Jurnal Harpodon Borneo, 2012)
Stock status of Yellowfin tuna in Indian Ocean on southern water of East Java currently is predicted undergoing overfishing or close to overfishing which is very alarming from sustainability context. A research has been done on Yellowfin tuna fisheries sustainability based on ecology, economy, technology, social and institutional dimensions. Collected data are analyzed using RAPFISH (multidimensional scaling/MDS, leverage analysis, monte carlo analysis), and comparison pairwess analysis to asses multidimensional sustainability of Yellowfin fisheries.Research result shows that Rapfish index for ecological sustainability is 57.83%, whereas economical, technological, social and institutional sustainability are consecutively: 68.14%, 98.03%, 44.89% and 47.88%. Multidimensional sustainability status assessment result show sustainability index 64.54 %, or Fairly Sustainable. Of those dimensions, social and institutional dimension have the lowest proportion in Yellowfin fisheries in Indian Ocean economic exclusive zone (EEZ) they are 7.63% and 4.24 %. Keywords: yellowfin tuna, sustainability, EEZ, Rapfish